Implementation and development needs for problem-based Value Clarification Technique (VCT) Model: Boosting grade 4 student’s learning interest and critical thinking - Christine Indahwati; Dewa Bagus Sanjaya; I Wayan Suastra (Research and Social Study Institute, 2025)
This study analyzes the implementation and development needs of a problem-based Value Clarification Technique (VCT)Model to enhance learning interest and critical thinking in Civic Education for fourth-grade elementary school students.Observations at one of Public Elementary School in Bali, Indonesia revealed conventional learning methods with limitedmedia and suboptimal implementation of problem-based issues, despite teachers' efforts to link material to local problems. Interviews confirmed teachers' limited understanding of VCT and their hopes for innovative models and media.Questionnaire results indicated low levels of student enjoyment and active engagement in Civic Education. These findings underscore the urgency of developing a problem-based VCT Model integrated with flashcards. This model iscrucial for shifting students' learning experiences toward concrete domains as per Edgar Dale's Cone of Experience, boosting learning interest, fostering critical thinking through problem-solving, and aligning with constructivist principles.This research provides a strong foundation for developing more effective and relevant Civic Education learning interventions.